Patients With Coronal Malalignment Undergoing Adult Spinal Deformity Surgery: Does Coronal Alignment Change From Immediately Postoperative to 2-years?. Issue 1 (14th February 2023) - Zuckerman, Scott L.; Chanbour, Hani; Hassan, Fthimnir M.; Lai, Christopher; Kerolus, Mena; Ha, Alex; Buchannan, Ian; Cerpa, Meghan; Lehman, Ronald A.; Lenke, Lawrence G.
Abstract : Study Design: Retrospective cohort study. Objectives: The objectives were to: (1) characterize the changes in coronal vertical axis (CVA) after adult spinal deformity (ASD) surgery from immediate postoperative to 2-years postoperative, and (2) assess for predictors of CVA change from immediate postoperative to 2-years postoperative. Summary of Background Data: It is unknown whether coronal correction obtained immediately postoperative accurately reflects long-term coronal alignment. Materials and Methods: A retrospective, single-institution registry was queried for patients undergoing ASD surgery from 2015-2019, including patients undergoing ≥6-level fusions with preoperative coronal malalignment (CM), defined as CVA≥3 cm. A clinically significant change in CVA was defined a priori as ≥1 cm. Radiographic variables were obtained preoperatively, immediately postoperative, and at 2-years postoperative. Results: Of 368 patients undergoing ASD surgery, 124 (33.7%) had preoperative CM, and 64 (17.0%) completed 2-years follow-up. Among 64 patients, mean age was 53.6±15.4 years. Preoperatively, absolute mean CVA was 5.4±3.1 cm, which improved to 2.3±2.0 cm ( P <0.001) immediately postoperative and 2.2±1.6 cm ( P <0.001) at 2-years. The mean change in CVA from preoperative to immediately postoperative was 2.2±1.9 cm (0.3–14.4). During the immediate postoperative to 2-years interval, 29/64 (45.3%) patients experienced a significant change of CVA by ≥1 cm, of which 22/29 (76%) improved by a mean of 1.7 cm and 7/29 (24%) worsened by a mean of 3.5 cm. No preoperative or surgical factors were associated with changed CVA from immediately postoperative to 2-years. Conclusion: Among 64 patients undergoing ASD surgery with preoperative CM, 45.3% experienced a significant (≥1 cm) change in their CVA from immediately postoperative to 2-years postoperative. Of these 29 patients, 22/29 (76%) improved, whereas 7/29 (24%) worsened. Although no factors were associated with undergoing a change in CVA, this information is useful in understanding the evolution and spontaneous coronal alignment changes that take place after major ASD coronal plane correction.